Role Conflict and Language Diversity in Indian Judiciary: Challenges and Opportunities in Justice Delivery under NEP Provisions - Singh, Shrikant (CV. Rayyan Dwi Bharata, 2025)
With an emphasis on Kanpur, this study examines the effects of role conflict and linguistic diversity within the Indian court, especially in relation to the National Education Policy (NEP) 2020. The primary aims of this study were to evaluate the opportunities and problems associated with the incorporation of regional languages in legal education and court processes, and to investigate the role conflict experienced by legal professionals as a result of this change. The study also sought to assess how technology can help to lessen these difficulties. Based on the findings, it was determined that as legal professionals balance the competing objectives of linguistic inclusivity and legal clarity, language variety does, in fact, contribute to role conflict among them, especially among judges, attorneys, and legal aid workers. This supports the hypothesis that the integration of regional languages would exacerbate role conflict. Moreover, while the NEP 2020 presents opportunities to enhance access to justice for non-English-speaking populations, the study identified significant challenges such as a lack of trained multilingual professionals, insufficient resources, and delays in proceedings due to translation issues. The study also highlighted that technological solutions, although useful, are not yet sufficient to fully overcome these language barriers. Despite their potential, AI-driven tools and translation services remain inadequate for handling the complexities of legal language in diverse regional contexts. To sum up, NEP 2020 provides a way forward for a more diverse judiciary, but realising its full potential will need significant funding for bilingual legal materials, enhanced legal education, and more sophisticated IT infrastructure. In order to ensure that the legal system can better serve India's linguistically diverse people, these reforms are crucial for striking a balance between linguistic inclusion and the requirement for legal precision and efficiency.